أثر نظام التكاليف على أساس الأنشطة في تحسين الإفصاح والشفافية - حمادي, نبيل; جلاخ, حسين (Université de M'sila, 2018)
The aim of this study is to identify the activities based on costs (ABC) system as a modern system of management accounting, and its impact to improve disclosure and transparency through the questionnaire method. The sample study represented by sample economic institutions and prac-titioners of auditing and accounting in order to estimate and test the multiple linear regression mod-el. This study concluded that is a tendency for the institutions to applies the (ABC) system, an-other significant result behind this study is the positive relationship between the application of the (ABC) system and improving disclosure and transparency. This study also recommended that eco-nomic institutions should accelerate the implementation of the system because of its effective role in Cost reduction and control; this allows the accurate inventories and sales cost evaluation that has positive reflect on the quality of the financial statements.
Keywords: .activités based costing system; transparency; disclosure